2022
DOI: 10.1073/pnas.2112546119
|View full text |Cite
|
Sign up to set email alerts
|

Development of DG9 peptide-conjugated single- and multi-exon skipping therapies for the treatment of Duchenne muscular dystrophy

Abstract: Significance Duchenne muscular dystrophy (DMD) is a fatal disorder of progressive body-wide muscle weakness, considered the most common muscular dystrophy worldwide. Most patients have out-of-frame deletions in the DMD gene, leading to dystrophin absence in muscle. There is no cure for DMD, but exon skipping is emerging as a potential therapy that uses antisense oligonucleotides to convert out-of-frame to in-frame mutations, enabling the production of truncated, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…We employed a cell-penetrating peptide DG9 derived from the PTD of the human Hph-1 transcription factor, since fusion proteins containing the Hph-1 domain are known to be delivered efficiently to a wide variety of tissues, including the heart (35). We recently demonstrated successful single and multi-exon skipping using DG9 conjugated to a different PMO cocktail targeting exons 45-55 in the dystrophin gene in vivo for the treatment of Duchenne muscular dystrophy (DMD) (54). Similar to our DMD findings, DG9-PMO treatment resulted in higher SMN expression in vivo compared to unconjugated PMO and MOE (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…We employed a cell-penetrating peptide DG9 derived from the PTD of the human Hph-1 transcription factor, since fusion proteins containing the Hph-1 domain are known to be delivered efficiently to a wide variety of tissues, including the heart (35). We recently demonstrated successful single and multi-exon skipping using DG9 conjugated to a different PMO cocktail targeting exons 45-55 in the dystrophin gene in vivo for the treatment of Duchenne muscular dystrophy (DMD) (54). Similar to our DMD findings, DG9-PMO treatment resulted in higher SMN expression in vivo compared to unconjugated PMO and MOE (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Exonic duplications and deletions within DMD are the main pathogenic variants ( 44 ), which has gained special interest as a new therapeutic method for DMD ( 45 ). It is reported that DMD exons 45-55 deletion has been postulated as a model that could treat up to 60% of DMD patients ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…This method improves the applicability of antisense therapy for DMD, and a cocktail skipping exons 45-55 has been validated in vitro and in vivo which could be applicable to nearly 50% of all DMD patients [69][70][71]. Furthermore, this research has demonstrated that spontaneous skipping can occur during multi-exon skipping which reduces the number of AONs required in the cocktail, reducing treatment complexity and cost [72]. At this time, the development of multi-exon skipping cocktails is limited by regulatory hurdles, as each AON in the cocktail must undergo separate clinical approval [24].…”
Section: Dyne-251mentioning
confidence: 94%